Longitudinal predictors for Mexican Americans' high school and college graduation: Individual and ecodevelopmental factors. Issue 2 (3rd April 2021) - Chapin, Laurie A.
ABSTRACT: This longitudinal study of Mexican-American youth and emerging adults examines several ecodevelopmental factors longitudinally predicting high school and college graduation. Data from 1257 Mexican-American youth (including those born in Mexico and whose families are from Mexico) from the National Longitudinal Study of Adolescent Health (Add Health) were utilized. Predictors were measured when participants were in grades 7 through 11 and high school and college graduation data was surveyed 13 years later. Individuals' aspirations and expectations about college, parent-child relationship quality, expectations for graduation, and friends' GPAs were the important predictors of both high school and college graduation. Friends' lack of substance use was also a significant predictor for college graduation. The longitudinal method and examining both high school and college graduations are useful and unique in this area of research, and therefore important for future research and interventions.